Analisis Tingkat Kebisingan pada Workshop Alsintan UPTD Balai Benih Induk Tanaman Pangan dan Alsintan Provinsi Lampung - Saputra, Muhamad Ogas; Suharyatun, Siti; Telaumbanua, Mareli; Warji, Warji (abe.fp.unila.ac.id, 2023)
Activities in agricultural machinery workshops must concern with Occupational Health and Safety (OHS), especially the physical conditions of the work environment. There are potential physical dangers, especially noise from machines in the workshop. This research aims to analyze the noise level at the UPTD Agricultural Machinery Workshop, Main Center for Food Crops and Agricultural Machinery, Lampung Province, and provides recommendations for control engineering. The parameters observed in the research were noise, temperature and humidity. Noise level was measured by using a sound level meter for the source of the sound when the machines were turned on, at fifty measurement points determined based on applicable regulations. Temperature and humidity were measured using a digital hygrometer thermometer, at three observation points. The measurement results were compared with the applied quality standards in Indonesia. Noise measurement resulted (88.29 ± 11.58) dBA, with 7 sound sources turned on simultaneously. Based on Minister of Manpower Regulation No. 5 of 2018, at this noise level the maximum exposure time for workers is 4 hours per day. If the time limit exceeds, workers must use ear protection or do the job in rotation (in shift work). Average temperature measurement resulted (28.8 ± 0.3)°C and average humidity measurement (61.5 ± 7.8)%. Referring to the Decree of the Minister of Health of the Republic of Indonesia No. 1405 of 2002, the air temperature and humidity at the UPTD Agricultural Machinery Workshop, Main Center for Food Crops and Agricultural Machinery, Lampung Province is still above the requirements for working environmental health. Keywords: Ergonomics, Noise, OHS, Physical Environment, Potential Physical Hazards.